Respuesta :

Answer:

[tex]x=11[/tex]

Step-by-step explanation:

So we have the equation:

[tex]\frac{-2-2x}{3} =-8[/tex]

First, multiply both sides by 3. This cancels out the denominator:

[tex]3(\frac{-2-2x}{3} )=3(-8)[/tex]

The left side cancels. Multiply the right:

[tex](-2-2x)=-24[/tex]

Add 2 to both sides. The 2s on the left cancel:

[tex](-2-2x)+2=(-24)+2\\-2x=-22[/tex]

Divide both sides by -2. The -2 on the left cancel.

[tex](-2x)/-2=(-22)/-2\\x=11[/tex]

Therefore, the answer is 11.

Answer:

x = 11

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

*(-2-2*x)/(3)-(-8)=0

Simplify:

*-2 - 2x  / 3

Pull out like factors:

*-2 - 2x  =   -2 • (x + 1)

Now It should look like this:

-2 • (x + 1) / 3 - (-8)  = 0

Rewrite the whole as a equivalent fraction using 3 as the denominator:

*-8 = -8 / 1 = -8 • 3 / 3

Add the two equivalent fractions which now have a common denominator

-Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

*-2 • (x+1) - (-8 • 3) / 3 = 22 - 2x / 3

Pull out like factors:

*22 - 2x  =   -2 • (x - 11)

Now you should have this:

*-2 • (x - 11)  / 3  = 0

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

-Now, to get rid of the denominator, multiply both sides of the equation by the denominator.

*-2•(x-11)  / 3 • 3 = 0 • 3

-Now, on the left hand side, the  3  cancels out the denominator, while, on the right hand side, zero times anything is still zero.

Now you should have this:

*-2  •  (x-11)  = 0

Now Solve:

x-11 = 0  

-Add  11  to both sides of the equation:

x = 11